HAEMATOLOGIC PROFILE REVISITED: ADULT CHOLISTANI BREEDING BULLS AS A MODEL - U. Farooq; Ijaz; A.; N. Ahmad; H. Rehman; H. Zaneb (Journal of Animal and Plant Sciences, 2012)
Cholistani breed of cattle is a Zebu (Bos indicus) or humped breed of Indian origin which has a remarkable potential of thermo-tolerance and tick-resistance. It is being reared by the nomadic herders of Cholistan desert of Pakistan under pastoral system and is a vital socio-economic asset of local nomads. A pilot study was conducted to assess various haematologic parameters in five adult Cholistani breeding bulls aged 5-11 years. These bulls were kept under naturally prevailing climatic conditions at Semen Production Unit, Karaniwala, Bahawalpur, Pakistan. Blood samples were aseptically collected fortnightly during October, 2011 to January, 2012 and analyzed for various haematologic parameters. Mean values for Hb, Total Erythrocyte Count, PCV, MCV, MCH and MCHC were 12.50 ± 0.40g/dL, 6.42 ± 0.31×106/µL, 37.18 ± 1.15%, 58.05 ± 1.58fL, 19.52 ± 0.51pg and 33.65 ± 0.79g/dL, respectively. Similarly, the mean Total Leukocyte Count was 7.80 ± 0.69×103/µL. Differential leukocyte count revealed that lymphocytes were the predominant leukocytes (50.55 ± 1.18%), followed by neutrophils (45.00 ± 1.38%) and monocytes (2.85 ± 0.18%), while eosinophils showed the lowest count (1.60 ± 0.17%). The present work is the first of its kind in Cholistani breeding bulls and the results can be used as a baseline reference haematologic data which in turn, will be helpful in monitoring the health status of these animals.
Keywords: Cholistan; Bos indicus; haematological profile.